Risk factors associated with myocardial infarction in venous thromboembolism patients. (January 2014) - Laliberté, F.; Nutescu, E. A.; Lefebvre, P.; Rondeau-Leclaire, J.; Bookhart, B. K.; LaMori, J. C.; Damaraju, C. V.; Schein, J.; Kaatz, S.
Abstract Background: Although risk factors for MI have been described in the general population, there is a lack of data on the assessment of risk factors associated with MI in venous thromboembolism (VTE) patients. Objective: The purpose of this study was to identify risk factors associated with MI in VTE patients. Patients and methods: Health insurance claims between January 2004 and September 2008 from the Ingenix IMPACT database were analyzed. Patients aged ≥18 years were identified as of the date of their first VTE diagnosis with ≥1 year of continuous insurance coverage before the index VTE. The risk of MI for VTE patients with 1, 2, and ≥3 major risk factors as identified by published guidelines was calculated. Multivariate Cox proportional hazard models were conducted to identify the most predictive risk factors associated with MI. Results: A total of 177, 885 VTE patients were identified; 4412 (2.5%) developed an MI during a mean follow-up period of 1.3 years. Previous MI, age (≥65 years), and coronary artery disease were the most predictive risk factors of MI with adjusted hazard ratios (HRs; 95% CI) of 5.47 (5.01–5.97), 1.78 (1.66–1.91), and 1.60 (1.48–1.74), respectively. Adjusted HRs (95% CI) for VTE patients with 1, 2, and ≥3 major risk factors relative to no major risk factor were 2.34 (1.94–2.81), 3.21 (2.67–3.85), and 6.93 (5.85–8.22), respectively. Limitations: These included possible inaccuracies or omissions in diagnoses, classification bias such as the identification of false-positive MI events, and the likely undercoding of some risk factors such as social issues. Conclusions: Traditional major cardiovascular risk factors are also predictive of MI in VTE patients. Having multiple major risk factors significantly increases the probability of developing MI events in VTE patients.